Chronic post-traumatic headache: clinical findings and possible mechanisms. (February 2014) - Defrin, Ruth
Abstract : Chronic post-traumatic headache (CPTHA), the most frequent complaint after traumatic brain injury (TBI), dramatically affects quality of life and function. Despite its high prevalence and persistence, the mechanism of CPTHA is poorly understood. This literature review aimed to analyze the results of studies assessing the characteristics and sensory profile of CPTHA in order to shed light on its possible underlying mechanisms. The search for English language articles published between 1960 and 2013 was conducted in MEDLINE, CINAHL, and PubMed. Studies assessing clinical features of headache after TBI as well as studies conducting quantitative somatosensory testing (QST) in individuals with CPTHA and in individuals suffering from other types of pain were included. Studies on animal models of pain following damage to peripheral tissues and to the peripheral and central nervous system were also included. The clinical features of CPTHA resembled those of primary headache, especially tension-type and migraine headache. Positive and negative signs were prevalent among individuals with CPTHA, in both the head and in other body regions, suggesting the presence of local (cranial) mechanical hypersensitivity, together with generalized thermal hypoesthesia and hypoalgesia. Evidence of dysfunctional pain modulation was also observed. Chronic post-traumatic headache can result from damage to intra- and pericranial tissues that caused chronic sensitization of these tissues. Alternatively, although not mutually exclusive, CPTHA might possibly be a form of central pain due to damage to brain structures involved in pain processing. These, other possibilities, as well as risk factors for CPTHA are discussed at length.